Haplotype analysis of the 4p16.3 region in Portuguese families with Huntington's disease. Issue 2 (5th February 2015) - Ramos, Eliana Marisa; Gillis, Tammy; Mysore, Jayalakshmi S.; Lee, Jong‐Min; Gögele, Martin; D'Elia, Yuri; Pichler, Irene; Sequeiros, Jorge; Pramstaller, Peter P.; Gusella, James F.; MacDonald, Marcy E.; Alonso, Isabel
Abstract : Huntington's disease (HD) is a neurodegenerative disorder characterized by involuntary choreic movements, cognitive impairment, and behavioral changes, caused by the expansion of an unstable CAG repeat in HTT . We characterized the genetic diversity of the HD mutation by performing an extensive haplotype analysis of ∼1Mb region flanking HTT in over 300 HD families of Portuguese origin. We observed that haplotype A, marked by HTT delta2642, was enriched in HD chromosomes and carried the two largest expansions reported in the Portuguese population. However, the most frequent HD haplotype B carried one of the largest (+12 CAGs) expansions, which resulted in an allele class change to full penetrance. Despite having a normal CAG distribution skewed to the higher end of the range, these two core haplotypes had similar expanded CAG repeat sizes compared to the other major core haplotypes (C and D) and there was no statistical difference in transmitted repeat instability across haplotypes. We observed a diversity of HTT region haplotypes in both normal and expanded chromosomes, representative of more than one ancestral chromosome underlying HD in Portugal, where multiple independent events on distinct chromosome 4 haplotypes have given rise to expansion into the pathogenic range. © 2015 Wiley Periodicals, Inc.